2023
DOI: 10.1101/2023.03.18.533283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The CARD8 inflammasome drives CD4+T-cell depletion in HIV-1 infection

Abstract: CD4+ T-cell depletion is the root cause of acquired immunodeficiency syndrome (AIDS). How HIV depletes CD4+ T cells in humans remains unknown because vast majority of the dying CD4+ T cells in patients are uninfected. Burgeoning evidence supports the hypothesis that non-productive HIV-1 infection triggers CD4+ T-cell depletion in the course of pathogenic HIV and SIV infections. Here, we report that the CARD8 inflammasome is activated immediately after HIV-1 entry by the viral protease encapsulated in the incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…However, as HIV-1 triggers CARD8 inflammasome activation as early as 2 hr post-infection, well before de novo synthesis of viral proteins ( Figure 4A ), our findings suggest that HIV-1 entry is also targeted by CARD8 via the innate immune detection of incoming viral protease activity. This conclusion is supported by a recent report that also found that HIV-1 strains lacking RT or integrase function are still sensed by the CARD8 inflammasome in a manner dependent on HIV-1 PR activity ( Wang and Shan, 2023 ). Based on these findings, we propose that CARD8 can sense HIV-1 PR that is packaged into the virion upon its release into the host cytosol upon viral fusion.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, as HIV-1 triggers CARD8 inflammasome activation as early as 2 hr post-infection, well before de novo synthesis of viral proteins ( Figure 4A ), our findings suggest that HIV-1 entry is also targeted by CARD8 via the innate immune detection of incoming viral protease activity. This conclusion is supported by a recent report that also found that HIV-1 strains lacking RT or integrase function are still sensed by the CARD8 inflammasome in a manner dependent on HIV-1 PR activity ( Wang and Shan, 2023 ). Based on these findings, we propose that CARD8 can sense HIV-1 PR that is packaged into the virion upon its release into the host cytosol upon viral fusion.…”
Section: Discussionsupporting
confidence: 61%
“…Our finding that HIV-1 infection is sufficient to induce inflammasome activation, along with the presence of CARD8 in relevant T cell populations ( Clark et al, 2022 ; Johnson et al, 2020 ; Linder et al, 2020 ), also suggests that CARD8 contributes to HIV pathogenesis. Consistent with this hypothesis, recent publications show that HIV-1 infection drives CARD8-dependent pyroptotic cell death both in primary human CD4+ T cells ex vivo and in humanized mouse models of HIV-1 ( Wang and Shan, 2023 ). It is also possible that IL-1β release after HIV-1-dependent CARD8 activation after HIV-1 infection could contribute to pathogenesis since IL-1β induces the differentiation of Th17 cells ( Chung et al, 2009 ), a highly HIV-susceptible CD4+ T cell subtype, as well as the recruitment of other target immune cells ( Rider et al, 2011 ).…”
Section: Discussionmentioning
confidence: 59%